EVALUASI DISTRIBUSI DOKTER DAN AKSES MASYARAKAT TERHADAP PELAYANAN MEDIS DI KABUPATEN GUNUNGKIDUL TAHUN 2010 - , Abdul Azis; , dr. Lutfan Lazuardi, M.Kes., PhD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. The lack number of medical provider and imbalanced distribution are the most relevant issues in human resource planning and manning which effected on the decreasing of health service indicator as the impact of lack of skillful and experienced manpower when the health service demand keeps increasing. Hence, evaluation on availability and distribution of medical service as a basic to create a policy on medical service arrangement in Gunungkidul district is necessary. Objective. This research was aimed to identify the availability and distribution on medical service as well community access in Gunungkidul district. Method. This was a case study research that was conducted in Gunungkidul district in February â April 2010 in Healh Office, Regional Employee Board, 3 government hospitals, 30 Primary Health Care and 111 branch Primary Health Care, 46 clinics and 51 private doctors. The data was collected from secondary data in 2008-2010 and in depth interview toward government authority who managed medical providers